Prevalence of Hepatitis B and C Viruses among Human Immunodeficiency Virus Infected Children Attending an Antiretroviral Therapy Clinic in Lafia, Nigeria - GR, Pennap; AJ, Yahuza; ML, Abdulkarim; VB, Oti (The Asia Journal of Applied Microbiology, 2017)
Nigeria has the largest burden of children living with HIV in the world but because of antiretroviral therapy, they are living longer. However, hepatitis B and C viruses are emerging important co-morbidities to consider especially for management decisions. This study set out to determine the prevalence of hepatitis B and C viruses among these children and to identify possible risk factors associated with the infections. Two hundred HIV-infected children at an antiretroviral treatment center were screened for Hepatitis B and C seromarkers using rapid test kits (ABCON Laboratories Hangzhou China). Informed written consent was obtained from their parents/guardian and information on their sociodemographics and exposure to some possible risk factors were obtained. A general prevalence of infection with hepatitis B and C virus in the study population was 14.0%. The prevalence of HBV was 3.0% while HCV was 11.0% and no child was coinfected with all 3 viruses. The HIV/HBV and HIV/HCV coinfection prevalence of 3.0% and 11.0% respectively is a cause for alarm. It is therefore pertinent that HIV infected children are screened for these viruses before commencement and during antiretroviral therapy.